Power, Luck and Ideology in a Model of Executive Pay - Peter Skott; Frederick Guy (University of Massachusetts, Department of Economics, 2013)
The microprocessor and related technologies have transformed corporate and industry structure; applied in a neo?liberal environment, the technologies have had profound effects on the relative power of different groups. Skott and Guy (2007) and Guy and Skott (2008) formalized one aspect of this process of power?biased technical change: firms' increased ability to monitor low?paid employees and the resulting changes in inequality and employment at the low end of the income distribution. This paper addresses power biases and income inequality at the high end. Increasing firm?level financial volatility has intensified the agency problem and increased the power of corporate executives. These effects, which have been compounded by changes in ideology and pay norms, yielded an explosion in executive pay. JEL Categories: J31, O33
Keywords: J31; O33; 330; communications technology; power-biased technical change; inequality; executive pay; efficiency wage